2011
DOI: 10.1016/j.mcm.2010.08.026
|View full text |Cite
|
Sign up to set email alerts
|

ViSim: A user-friendly graphical simulation tool for performance analysis of MANET routing protocols

Abstract: a b s t r a c tThe task of simulation is often complicated, and naive users often look for relatively easier solutions. In many cases, simulations are done with no visual output which makes them non-attractive. In this paper, we present ViSim; a new simulation tool that has a userfriendly graphical interface. ViSim could be useful for researchers, students, teachers in their work, and for the demonstration of various wireless network scenarios on computer screens. It could make the task of simulation more exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[12]. Saquib et al developed a new simulation tool with the Visual basic programing language due to the challenges of working with Ns-2 [13].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[12]. Saquib et al developed a new simulation tool with the Visual basic programing language due to the challenges of working with Ns-2 [13].…”
Section: Related Workmentioning
confidence: 99%
“…[12]. Saquib et al developed a new simulation tool with the Visual basic programing language due to the challenges of working with Ns-2 [13]. Kim et al aimed to make a better simulation study using the relative advantages of DEVS and Ns-2 with respect to each other [14].…”
Section: Related Workmentioning
confidence: 99%
“…In literature, several tools and methodologies are used for studying the CPS performance that include specific aspect of CPS such as network performance, processor scheduling, or physical system properties. For instance, Network Simulator NS-2 [28], has the capability to add different protocols for all combinations of networks [34]. Visim [26] is another tool that uses NS-2 internally, but simplifies the task of simulating Mobile ad-hoc Wireless Network routing protocols.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Network Simulator NS-2 [28], has the capability to add different protocols for all combinations of networks [34]. Visim [26] is another tool that uses NS-2 internally, but simplifies the task of simulating Mobile ad-hoc Wireless Network routing protocols. Authors demonstrated the performance of different routing prtocols.…”
Section: Introductionmentioning
confidence: 99%